Current and Future Trends of Silk Fibroin-Based Bioinks In 3D Printing - Oliveira, Joaquim M (Journal of 3D printing in medicine, 2020)
Despite the promising achievements in personalized tissue engineering due to recent advances in 3D bioprinting, we still face several challenges in the field. 3D bioprinting methods still possess several limitations related to: nozzle clogs; the fact that heating-based systems can damage both protein-based inks and encapsulated cells; methods are time consuming; and the poor resolution and lack of control over spatial distribution, in particular for achieving a 3D single-cell with surrounding ECM and high-resolution printing. [...]finding the right bioink and biofabrication method is a difficult and complex process, as the biomaterial/bioink must: be processable using available biofabrication instruments and techniques; be biocompatible with target tissues; not be immunogenic or toxic, to both host and transplanted cells; allow the combination of in vivo imaging and surgical methods; and have a production and printing process that is cost-effective and fairly easy for the user, in order to facilitate translation to the clinical setting. SF purified from sericins by boiling silk cocoons in an alkaline solution, for example (9), has been attracting a great deal of interest as a biomaterial due to its biocompatibility, well-controlled degradability and versatile processability, thus being suitable for bioink preparation. [...]they can be processed as injectable hydrogels and have tunable mechanical properties, which are ideal for drug/cell encapsulation and delivery. The eSF hydrogels were proposed as artificial biomimetic 3D matrices for different tissue-engineering applications, including hierarchical scaffolds, showing cell seeding, encapsulation and differentiation potential (30). [...]eSF hydrogels possess tunable mechanical and degradation properties and biological performance depending on how they are processed and according to the formulation of SF solution/enzyme/cross-linker or oxidizer concentrations. [...]the possibility of controlling the conformational changes from random coils to β-sheets in the HRP-cross-linked SF hydrogels, and improving their structural stability as bioinks and injectable matrices, will make these systems fundamental for